2017
DOI: 10.1111/pim.12424
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ovine peripheral blood mononuclear cells on Haemonchus contortus larval morbidity in vitro

Abstract: The objective of this study was to determine the effects of peripheral blood mononuclear cells (PBMC), derived from parasite-resistant St. Croix (STC) hair sheep and parasite-susceptible Suffolk (SUF) sheep, on Haemonchus contortus L stage larval death in vitro, with or without autologous serum. Larval morbidity was quantified by measuring larval ATP concentration following incubation with PBMC. Larvae exposed to either STC- or SUF-derived PBMC had lower ATP than live larvae (0.12 μmol/L ATP and 0.16 μmol/L AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Similar responses have been observed in ovine gastrointestinal nematode in vitro models, H. contortus infected STC PBMC (composed of monocytes and lymphocytes) cultured with larvae led to a reduction in larval motility (Holt et al, 2015). Quantifying larval death after culture with PBMC by ATP quantification further found a greater reduction in larval ATP when cultured with STC PBMC than SUF PBMC (Shepherd et al, 2017).…”
Section: Immune Response To Haemonchus Contortussupporting
confidence: 69%
“…Similar responses have been observed in ovine gastrointestinal nematode in vitro models, H. contortus infected STC PBMC (composed of monocytes and lymphocytes) cultured with larvae led to a reduction in larval motility (Holt et al, 2015). Quantifying larval death after culture with PBMC by ATP quantification further found a greater reduction in larval ATP when cultured with STC PBMC than SUF PBMC (Shepherd et al, 2017).…”
Section: Immune Response To Haemonchus Contortussupporting
confidence: 69%
“…There were no differences in ATP levels of L3 exposed to challenged Suffolk neutrophils compared to live controls. While the ATP levels of primed St. Croix neutrophil‐exposed larvae were higher than heat‐killed larvae, ATP levels were below the threshold for larval morbidity previously established (Figure C).…”
Section: Resultsmentioning
confidence: 56%
“…Our laboratory has previously shown that ovine peripheral blood mononuclear cells impair L3 motility quantified by decreases in both movement and ATP levels in vitro . We next sought to evaluate the ability of larval‐bound neutrophils to similarly impair their targets by measuring larval ATP after exposure to challenged St. Croix and Suffolk‐derived cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous data have indicated that ovine PBMC can severely inhibit Hc larval motility and increase larval morbidity 17,18 . Therefore, the objective of this study was to determine which cell subset of PBMC contributes to larval morbidity using ATP quantification.…”
Section: Introductionmentioning
confidence: 99%